The management of secondary pelvi‐ureteric junction obstruction – a comparison of pyeloplasty and endopyelotomy. (January 2014) - Vannahme, Milena; Mathur, Sunil; Davenport, Kim; Timoney, Anthony G.; Keeley, Francis X.
<x xml:space="preserve">Abstract</x> Objective To review our experience in the management of secondary pelvi‐ureteric junction obstruction (PUJO) comparing endopyelotomy with pyeloplasty. Patients and Methods We retrospectively analysed our database of 58 patients having undergone operative management of PUJO after failed primary management, including 41 with failed pyeloplasty and 17 failed endopyelotomy. Outcomes included mercapto‐acetyltriglycine (MAG3) drainage capacity, symptomatic control and need for further intervention. Success was defined as freedom from failure in all three. Results Patients undergoing secondary pyeloplasty had better outcomes than endopyelotomy for symptomatic success (87.5% vs 74%), resolution of obstruction on MAG3 renography (96% vs 74%), and no need for further intervention (96% vs 71%). Overall success was 87.5% for pyeloplasty compared with 44% after secondary endopyelotomy. Conclusion Outcomes of pyelopasty for secondary PUJO were superior when compared with endopyelotomy.